2021
DOI: 10.1111/jonm.13355
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perception about Human Resource Management system and prosocial organisational behaviour: Mediating role of job efficacy

Abstract: Aims To examine the relationship between nurses' perception about human resource management system and prosocial organisational behaviour through job efficacy. Background Literature suggests that non‐profit organisations are often confronted with financial constraints on one side and the expectation of delivering high‐quality services on the other. Employees voluntarily engaging in service‐oriented behaviours help to bridge this gap to some extent, and human resource management system plays a significant role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
2
6
0
Order By: Relevance
“…For instance, Lahlouh et al (2023) have noted that safety coaching plays a vital role in organizations as a diminisher of employees' emotional exhaustion. Moreover, when engrained in organizational culture and climate, safety coaching can also foster prosocial organizational behaviors (Luthufi et al, 2020). The findings from the current study extend this work and indicate that safety coaching impacts another crucial work-related outcome, namely, work engagement.…”
Section: Safety Coaching and Work Engagementsupporting
confidence: 79%
See 2 more Smart Citations
“…For instance, Lahlouh et al (2023) have noted that safety coaching plays a vital role in organizations as a diminisher of employees' emotional exhaustion. Moreover, when engrained in organizational culture and climate, safety coaching can also foster prosocial organizational behaviors (Luthufi et al, 2020). The findings from the current study extend this work and indicate that safety coaching impacts another crucial work-related outcome, namely, work engagement.…”
Section: Safety Coaching and Work Engagementsupporting
confidence: 79%
“…For instance, Lahlouh and colleagues have found that safety coaching helps organizations by diminishing emotional exhaustion among their employees (Lahlouh et al, 2023). Moreover, when engrained in organizational culture and climate, safety coaching can also foster prosocial organizational behaviors (Luthufi et al, 2020). Importantly, empirical evidence also indicates that an organization's investment in other safety initiatives, such as developing a safety climate, leads to both safety-related and non-safety-related outcomes, e.g.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…In the etic studies, using a variety of established instruments and measures, there was little consistency with the prosocial and work-related constructs they did use [ 37 , 38 , 39 , 40 , 41 , 42 ]. Organization Citizenship Behavior (OCB) was cited twice.…”
Section: Resultsmentioning
confidence: 99%
“…A growing number of scholars have made efforts to better align OB, HR and nursing research. As examples, Renkema et al (2021) investigated how high-involvement HR influences nurses' innovative behavior, and Luthufi et al (2021) examined the link between nurses' perceptions of HR and prosocial OB. However, scholarship has largely remained isolated within fields.…”
Section: A Case For Communication Across Literaturementioning
confidence: 99%